A pressure-free and firing-free brick for collaboratively recovering solid waste molten water quenching slag and sludge incineration ash and a preparation method thereof
By collaboratively recycling solid waste molten water quenching slag and sludge incineration ash, and using alkali excitation and casting forming processes, high-strength pressure-free and burn-free bricks are prepared, which solves the problems of high energy consumption and large carbon emissions in solid waste disposal and traditional brick making methods, and achieves efficient solid waste resource utilization and low-carbon and environmentally friendly production processes.
Patent Information
- Application Number
- CN202411830123.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The output of solid waste molten water quenching slag and sludge incineration ash is huge and lacks resource-based disposal methods. The traditional high-temperature sintering brick making method has high energy consumption and large carbon emissions, and the heavy metal leaching of solid waste building materials products is high and the performance is poor.
By collaboratively recovering solid waste molten water quenching slag and sludge incineration ash, using scientific compatibility with raw material ratios and alkali excitation methods, combined with casting molding technology, high-strength pressure-free and burn-free bricks are prepared.
The chemical composition of water quenching slag and sludge incineration ash is complementary, the efficient fixation of heavy metals, and the mechanical properties of bricks are improved, and the production of high strength and durability is not burned-free bricks are reduced, reducing the energy consumption and carbon emissions of traditional brick making methods.
Smart Images

Figure CN119285288B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of safe disposal and resource utilization of solid waste, and in particular to a pressure-free and firing-free brick for collaboratively recovering solid waste molten water-quenched slag and sludge incineration ash and a preparation method thereof. Background Art
[0002] High-temperature melting technology is a mature technology for the treatment and disposal of hazardous waste. It can not only achieve efficient extraction of precious metals from solid waste, but also stabilize heavy metals through glass solidification, thereby achieving the reduction, resource utilization and harmless disposal of hazardous waste. The hazardous waste smelting process inevitably produces a large amount of high-temperature molten water-quenched slag (hereinafter referred to as "water-quenched slag"), which has a certain risk of heavy metal leaching, and has a large stockpile, low degree of harmless disposal and value-added utilization. If it is not properly handled, it will bring great pressure to environmental safety. Water-quenched slag is mainly composed of components such as active silicate, and has the potential to prepare cementitious materials for building material utilization. Because its particle size is not much different from that of natural sand, it is often used to replace natural sand as fine aggregate. However, due to the rough surface and irregular shape of water-quenched slag, using it as aggregate will seriously reduce the fluidity of mortar and cause the deterioration of the microstructure of mortar, so it cannot meet the requirements of construction sand. At the same time, because water-quenched slag contains more heavy metals and other pollutants, its large-scale disposal and resource utilization are greatly limited. Therefore, the current effective utilization rate of water-quenched slag is extremely low, and the main treatment method is landfill. Considering the saturation of safe landfill sites and long-term safety issues, landfill disposal no longer meets the requirements of sustainable development. It is urgent to find efficient and safe innovative ways to achieve large-scale disposal and resource utilization of solid waste molten water-quenched slag.
[0003] Wall bricks are an indispensable and huge material in the construction field. Their production methods mainly include high-temperature calcination molding and pressing molding. Among them, the more mature high-temperature calcination process can convert solid waste rich in aluminosilicate minerals (such as clay, fly ash, etc.) into high-strength sintered bricks. However, the energy consumption and carbon emissions of the firing process are high, which is costly for the resource utilization of solid waste. At the same time, for some solid wastes (such as water-quenched slag and sludge incineration ash), there are problems of volatilization of pollutants such as heavy metals during high-temperature treatment, which will cause corrosion of related equipment and secondary environmental pollution. Therefore, this method is not suitable for the resource disposal of solid wastes such as water-quenched slag and sludge incineration ash. Therefore, it is urgent to use water-quenched slag and sludge incineration ash for coordinated disposal at room temperature, and actively develop environmentally friendly unburned bricks based on water-quenched slag and sludge incineration ash as a substitute for ordinary high-temperature sintered bricks. Combining the resource utilization of solid waste with the production of unburned bricks has good application prospects and promotion potential, both for the development of the construction industry and for meeting the actual needs of absorbing a large amount of solid waste.
[0004] The manufacturing methods of unfired bricks mainly include casting and pressing, among which the most common and mature one is pressing. However, the pressing process is relatively complicated and accompanied by a certain amount of energy consumption. The casting process does not require high-pressure pressing. It mainly uses the hydration reaction of the binder and the geological polymerization reaction of the volcanic ash material to improve the strength of the brick body. It is a low-carbon, energy-saving and environmentally friendly unfired brick manufacturing process. At the same time, the amorphous aluminosilicate gels such as hydrated calcium aluminosilicate and hydrated sodium aluminosilicate produced by the hydration reaction can fix pollutants through various physical and chemical mechanisms such as physical encapsulation, chemical adsorption, and covalent bonding. Therefore, casting brick making is an important development direction for achieving efficient detoxification of water-quenched slag and value-added utilization of building materials. At the same time, compared with the pressing technology, the low-carbon and environmentally friendly characteristics of the casting technology make it more promising in the field of solid waste resource utilization.
[0005] Compared with other solid wastes (coal gangue, metallurgical slag, non-coal tailings, etc.), water-quenched slag itself has a high content of calcium, silicon, and aluminum phase components, and its CaO content is about 30%-35% of the dry mass of water-quenched slag, which has the potential for use as building materials. The water-quenched slag powder with a certain fineness obtained by mechanochemical grinding can effectively stimulate the reactivity of the calcium, silicon, and aluminum phase components in the water-quenched slag. In addition, a large amount of sludge incineration ash produced during the sludge drying and incineration process contains rich SiO2, Al2O3, Fe2O3 and other components, has a certain volcanic ash reactivity, and can provide silicon and aluminum phase components as a precursor. By utilizing the different phase components of water-quenched slag and sludge incineration ash, the chemical composition advantages of the two can be complemented by scientific matching, and it has the potential for synergistic recovery and preparation of alkali-activated cementitious materials, but related exploration and research are still lacking. Therefore, it is urgent to find a method for synergistic treatment of multi-source solid waste water-quenched slag and sludge incineration ash.
[0006] The present invention has the following technical problems:
[0007] 1) The output of solid waste molten water quenching slag and sludge incineration ash is huge, and there is a lack of resource disposal methods, making it difficult to dispose of them in large quantities;
[0008] 2) The traditional high-temperature sintering and pressing brick making methods have complex operation processes, high energy consumption and carbon emissions;
[0009] 3) Solid waste building material products have a high risk of heavy metal leaching, poor product performance, and limited application. Summary of the invention
[0010] The purpose of the present invention is to propose a pressure-free and unburned brick that synergistically recycles solid waste molten water-quenched slag and sludge incineration ash and a preparation method thereof, and to utilize the water-quenched slag and sludge incineration ash as building materials to prepare high-strength unburned bricks. By utilizing the chemical composition complementarity mechanism between the two solid wastes, through scientific formula design and combined with process route optimization, the efficient fixation of heavy metals and the improvement of the mechanical properties of the brick body are achieved, and unburned bricks with high strength and good durability are produced.
[0011] To achieve the above object, the present invention proposes a method for producing unburned bricks by casting and molding process using solid waste molten water quenching slag, sludge incineration ash, recycled aggregate, alkali activator and deionized water as raw materials. The present invention is achieved by the following technical solutions:
[0012] The invention discloses a pressure-free and unfired brick for collaboratively recovering solid waste molten water-quenched slag and sludge incineration ash. The pressure-free and unfired brick uses hydrated calcium aluminosilicate gel and hydrated sodium aluminosilicate gel as main hydration products. The raw material formula is, by mass, solid waste molten water-quenched slag: sludge incineration ash: recycled aggregate: alkaline stimulating liquid = 3.0-7.0: 7.0-3.0: 10.0: 7.0.
[0013] As a further improvement, the unfired bricks described in the present invention have a compressive strength of 24.3 to 33.6 MPa, a 24-hour water retention strength of 18.8 to 28.5 MPa, a flexural strength of 3.4 to 4.7 MPa, and a 24-hour water absorption rate of less than 15%.
[0014] The present invention also discloses a method for preparing pressure-free and firing-free bricks for collaboratively recovering solid waste molten water quenching slag and sludge incineration ash, comprising the following steps:
[0015] S1: placing the solid waste molten water-quenched slag in a ball mill, adding gypsum or grinding aids not exceeding 0.5% of the mass of the solid waste molten water-quenched slag, and grinding to the solid waste molten water-quenched slag powder of a specified fineness;
[0016] S2: The solid waste molten water quenched slag powder, the sludge incineration ash, and the recycled aggregate are uniformly mixed in a mass ratio of 3.0-7.0: 7.0-3.0: 10.0 to obtain a mixed dry material, wherein the solid waste molten water quenched slag powder and the sludge incineration ash need to be dried to a constant weight before mixing;
[0017] S3: preparing an alkaline stimulating solution by mixing alkaline stimulating agent: deionized water in a ratio of 4.0-4.5: 3.0-2.5;
[0018] S4: mixing the prepared alkaline stimulating liquid with the mixed dry material and stirring to obtain a fresh slurry, then pouring it into a mold for vibration molding, and curing it under sealed conditions;
[0019] S5: After short-term sealed curing, the blocks with a certain initial strength are demoulded and placed under standard conditions for curing for 25-30 days to obtain the unfired brick product.
[0020] As a further improvement, in step S1 of the present invention, the water content of the solid waste molten water quenched slag is ≤10%, the ball milling speed is 300-450 r / min, and the time is 1-2 h.
[0021] As a further improvement, the gypsum in step S1 of the present invention complies with the gypsum or mixed gypsum of Class G or Class M Grade 2 (inclusive) or above specified in GB / T 5483, and the grinding aid complies with the provisions of GB / T 26748.
[0022] As a further improvement, the particle size of the solid waste molten water-quenched slag powder in step S1 of the present invention includes a pass rate of 100% through a 100-mesh sieve, a pass rate of not less than 90% through a 150-mesh sieve, and a pass rate of not less than 55% through a 300-mesh sieve.
[0023] As a further improvement, the recycled aggregate in step S2 of the present invention is any one of waste concrete, waste bricks, waste ceramics, etc., or a mixture of several of them.
[0024] As a further improvement, in step S2 of the present invention, the particle size of the recycled aggregate is continuously graded between 2.36 mm and 9.5 mm, wherein the mass ratio of aggregates with particle sizes of 2.36 mm to 4.75 mm and 4.75 mm to 9.5 mm is 1:1.
[0025] As a further improvement, in step S3 of the present invention, the alkaline activator is solid sodium hydroxide and liquid sodium silicate in a mass ratio of 0.5:4.0; the purity of the solid sodium hydroxide is greater than 98%; the mass fraction of sodium oxide in the liquid sodium silicate solution is 10%, the mass fraction of silicon dioxide is 30%, and the mass fraction of water is 60%.
[0026] As a further improvement, during the mixing and stirring in step S4 of the present invention, the stirring time of the stirrer is 2-3 min and the rotation speed is 300 r / min.
[0027] As a further improvement, during the vibration forming in step S4 of the present invention, the vibration amplitude is ≤ 5 mm, the vibration frequency is 18 to 24 times / min, and the vibration time is 10 to 15 s.
[0028] As a further improvement, the step S4 described in the present invention is cured under sealed conditions for 24 hours, specifically, sealed curing for 24 hours at an ambient temperature of 20±2°C.
[0029] As a further improvement, the standard curing temperature in step S5 of the present invention is 20±2°C, the relative humidity is above 95%, and the time is 25 to 30 days.
[0030] As a further improvement, the present invention tests the unfired brick according to GB / T 2542-2012 "Test Methods for Wall Bricks", and the compressive strength is 24.3-33.6 MPa, the water retention strength is 18.8-28.5 MPa, the flexural strength is 3.4-4.7 MPa, and the water absorption rate is less than 15%.
[0031] Features and beneficial effects of the present invention:
[0032] The present invention provides a new way to safely dispose of and recycle solid waste molten water quenching slag, and utilizes solid waste molten water quenching slag, sludge incineration ash, recycled aggregate, alkali activator and other raw materials, and manufactures all-solid waste-based pressure-free and fire-free bricks based on alkali activation, casting, standard maintenance and other means, which not only meets the brick standards of the building materials industry, but also realizes the large-scale disposal and resource disposal of solid waste;
[0033] The present invention utilizes water-quenched slag and sludge incineration ash in a coordinated manner to transform them into pressure-free and fire-free bricks. The present invention achieves the mechanism complementarity of the chemical composition of water-quenched slag and sludge incineration ash and the large-scale disposal and building material utilization of these two solid wastes by scientifically matching the raw material ratios, i.e., water-quenched slag powder: sludge incineration ash: recycled aggregate: alkaline stimulating liquid = 3.0-7.0: 7.0-3.0: 10.0: 7.0; by adding a certain proportion of recycled aggregate, the stability of the brick body can be increased; by optimizing the particle grading of the added recycled aggregate, the fluidity of the original slurry of the fire-free brick can be regulated, the processing performance of the fire-free brick is improved, the density of the brick body is increased, and a new resource disposal method for recycled aggregate is provided; at the same time, the present invention adopts an energy-saving and environmentally friendly casting and molding brick-making process, which reduces the preparation steps and corresponding energy consumption of traditional high-temperature sintering brick-making and pressing and molding brick-making, and significantly reduces the production cost and carbon emissions of wall bricks;
[0034] The present invention firstly grinds the solid waste molten water-quenched slag by mechanochemical method, which can effectively stimulate the reaction activity of calcium-silicon-aluminum phase components in the water-quenched slag. By adding gypsum or grinding aid for ball milling, the ball milling efficiency is improved and the energy consumption is reduced; by adjusting the ball milling speed and time of the ball mill, the fineness and reaction activity of the water-quenched slag powder are guaranteed;
[0035] The present invention effectively activates the two solid wastes, water-quenched slag and sludge incineration ash, by using an alkali excitation method. The alkaline excitation liquid used can quickly and effectively excite the volcanic ash activity of the solid waste molten water-quenched slag and sludge incineration ash, promote their reaction degree and strength development, and improve the bonding degree between the cementitious material and the recycled aggregate. The alkaline exciter is composed of sodium hydroxide and liquid sodium silicate. By adjusting the ratio of sodium hydroxide and liquid sodium silicate to deionized water, a suitable alkaline environment is provided for the solid waste system. Liquid sodium silicate can also provide certain active silicate ions for the generation of aluminosilicate gel in the system. Under the activation of the alkaline exciter, the raw materials such as water-quenched slag and sludge incineration ash are dissolved to generate silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron monomers, and then through polycondensation reaction, they are combined with alkali metal ions such as calcium and sodium in the system to form a cross-linked aluminosilicate gel with a three-dimensional network structure (hydrated calcium aluminosilicate and hydrated sodium aluminosilicate gel cross-linked). As the reaction proceeds, the amount of gel generated gradually increases and the structure gradually becomes dense, which makes the unburned brick have a higher density and skeleton strength. In addition, reaction products such as aluminosilicate gel produced by hydration reactions also achieve in-situ solidification of endogenous heavy metals in raw materials: toxic pollutants such as heavy metals in water-quenched slag and sludge incineration ash are stably solidified in the cementitious material matrix through the synergistic action of multiple physical and chemical mechanisms such as physical encapsulation, ion exchange, and covalent bonding.
[0036] Finally, the pressure-free and firing-free bricks prepared by the present invention with water-quenched slag, sludge incineration ash and recycled aggregate as main raw materials have a compressive strength of 24.3-33.6 MPa, a water retention strength of 18.8-28.5 MPa, a flexural strength of 3.4-4.7 MPa, a water absorption rate of less than 15%, and the size deviation, appearance and color difference all meet the requirements of qualified products specified in C / T 422-2007 "Non-fired garbage tailings bricks", and can replace ordinary fired bricks as building materials such as wall bricks and concrete pavement bricks. In general, on the one hand, the present invention reduces the use of traditional brick-making raw materials, and the casting molding technology adopted has low energy consumption and less carbon emissions, and has the advantages of green economy; on the other hand, it effectively absorbs two types of solid waste, water-quenched slag and sludge incineration ash, and converts them into unfired brick value-added building materials. Compared with the traditional safe landfill treatment method, the present invention further develops the secondary utilization value of solid waste, and also realizes the efficient detoxification of water-quenched slag, which has both environmental benefits and socio-economic benefits, and provides a new sustainable development plan for the resource utilization of solid waste and the green transformation of the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of the process of preparing pressure-free and firing-free bricks by synergistically recycling solid waste molten water-quenched slag and sludge incineration ash in an embodiment of the present invention. DETAILED DESCRIPTION
[0038] The present invention provides a pressure-free and unburned brick for collaboratively recovering solid waste molten water quenching slag and sludge incineration ash and a preparation method thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0039] The embodiment of the present invention provides a method for preparing pressure-free and firing-free bricks using solid waste molten water quenching slag and sludge incineration ash as main raw materials, such as Figure 1 As shown in the figure, RH: relative humidity.
[0040] In some specific implementations, in order to prevent the raw materials from getting damp and agglomerating, thereby causing uneven mixing, the water-quenched slag and sludge incineration ash need to be pre-dried before the raw materials are mixed to keep them in a uniform powder state.
[0041] In some specific embodiments, in order to compare the effects of the ratio of the cementitious materials used in the present invention (the ratio of water-quenched slag to sludge incineration ash) and the ratio of the alkaline activator to deionized water in the alkaline activating solution on the physical properties of unfired bricks, relevant data of unfired bricks produced by using eight different ratios of cementitious materials and different ratios of alkaline activators to deionized water are provided.
[0042] The original contents of heavy metals in the solid waste molten water quenching slag and sludge incineration ash used in the following examples and comparative examples are shown in Table 1. (Tested in accordance with GB 5085.3-2007 "Identification Standard for Hazardous Waste Identification - Leaching Toxicity Identification", the unit of heavy metal ions is mg / L)
[0043] Table 1 Heavy metal leaching concentrations of solid waste molten water quenched slag and sludge incineration ash
[0044] heavy metal Zn Pb Mn Cr Cd As Ni Cu Solid waste molten water quenching slag 1.945 0.241 15.840 0.055 0.004 0.563 4.135 0.056 Sludge incineration ash 1.511 0.064 2.443 0.067 0.093 0.003 0.065 0.121
[0045] The following is a further explanation of the pressure-free and firing-free bricks and the preparation method thereof for realizing the coordinated recycling of solid waste molten water quenching slag and sludge incineration ash proposed by the present invention through specific embodiments: Example 1
[0046] A pressure-free and firing-free brick prepared by synergistically recycling solid waste molten water quenching slag and sludge incineration ash, according to Figure 1 The specific steps are as follows:
[0047] 1) Place the water-quenched slag in a ball mill and mill it at a speed of 450 r / min for 1-2 h, and sieve the obtained water-quenched slag powder (100 mesh).
[0048] 2) Weigh the water-quenched slag powder and sludge incineration ash, place them in an oven, and dry them at 105 °C to constant weight;
[0049] 3) The water-quenched slag powder, sludge incineration ash and recycled aggregate were uniformly mixed in a mass ratio of 7.0:3.0:10.0, and stirred for 1 min (at a speed of 300 r / min) to obtain a mixed dry material.
[0050] 4) Solid sodium hydroxide and liquid sodium silicate are mixed in a mass ratio of 0.5:4.0 to prepare an alkali activator.
[0051] 5) Prepare an alkaline stimulating solution by mixing alkaline stimulating agent and deionized water in a ratio of 4.5:2.5 and let it stand for 24 hours.
[0052] 6) The prepared alkaline stimulating liquid and the mixed dry material are mixed in a ratio of 7.0:20.0 and stirred to obtain a fresh slurry (stirring for 2-3 min, rotating speed of 300 r / min), then poured into a 240 mm×115 mm×53 mm mold for vibration molding (vibration amplitude ≤ 5 mm, vibration frequency of 18-24 times / min, vibration time of 10-15 s), and then placed at 20±2 °C under sealed conditions for curing for 24 hours.
[0053] 7) After short-term curing, the blocks with a certain initial strength are demoulded and placed under standard conditions (temperature of 20±2 °C, relative humidity of more than 95%) for curing for 25-30 days to obtain the unfired brick products.
[0054] 8) After the curing period, the heavy metal leaching concentration of the product bricks was tested according to GB 5085.3-2007 "Identification Standard for Hazardous Waste Leaching Toxicity Identification", and the test results are shown in Table 2:
[0055] Table 2 Heavy metal leaching concentration of the cementitious material of Example 1
[0056] heavy metal Zn Pb Mn Cr Cd As Ni Cu Example 1 (heavy metal leaching concentration mg / L) 0.006 0.011 0.001 0.003 0.000 0.075 0.001 0.005
[0057] The obtained bricks were tested for performance according to GB / T 2542-2012 "Test Methods for Wall Bricks". The test results of the physical properties of the bricks are shown in Table 3:
[0058] Table 3 Physical properties of pressure-free and unfired bricks of Example 1
[0059] Example 2
[0060] A pressure-free and firing-free brick prepared by synergistically recycling solid waste molten water quenching slag and sludge incineration ash, according to Figure 1 The specific steps are as follows:
[0061] 1) Place the water-quenched slag in a ball mill and mill it at a speed of 450 r / min for 1-2 h, and sieve the obtained water-quenched slag powder (100 mesh).
[0062] 2) Weigh the water-quenched slag powder and sludge incineration ash, place them in an oven, and dry them at 105 °C to constant weight;
[0063] 3) The water-quenched slag powder, sludge incineration ash and recycled aggregate were uniformly mixed in a mass ratio of 5.0:5.0:10.0, and stirred for 1 min (at a speed of 300 r / min) to obtain a mixed dry material.
[0064] 4) Prepare an alkali activator by mixing solid sodium hydroxide and liquid sodium silicate in a mass ratio of 0.5:4.0.
[0065] 5) Prepare an alkaline stimulating solution by mixing alkaline stimulating agent and deionized water in a ratio of 4.5:2.5 and let it stand for 24 hours.
[0066] 6) The prepared alkaline stimulating liquid and the mixed dry material are mixed in a ratio of 7.0:20.0 and stirred to obtain a fresh slurry (stirring for 2-3 min, rotating speed of 300 r / min), then poured into a 240 mm×115 mm×53 mm mold for vibration molding (vibration amplitude ≤ 5 mm, vibration frequency of 18-24 times / min, vibration time of 10-15 s), and then placed at 20±2 °C under sealed conditions for curing for 24 hours.
[0067] 7) After short-term curing, the blocks with a certain initial strength are demoulded and placed under standard conditions (temperature of 20±2 °C, relative humidity of more than 95%) for curing for 25-30 days to obtain the unfired brick products.
[0068] 8) After the curing period, the heavy metal leaching concentration of the product brick cementitious material is tested according to GB 5085.3-2007 "Identification of Hazardous Waste Identification Standard Leaching Toxicity Identification", and the test results are shown in Table 4:
[0069] Table 4 Heavy metal leaching concentration of the cementitious material of Example 2
[0070] heavy metal Zn Pb Mn Cr Cd As Ni Cu Example 2 (heavy metal leaching concentration mg / L) 0.008 0.009 0.029 0.006 0.000 0.031 0.011 0.007
[0071] The obtained bricks were tested for performance according to GB / T 2542-2012 "Test Methods for Wall Bricks". The test results of the physical properties of the bricks are shown in Table 5:
[0072] Table 5 Physical properties of pressure-free and unfired bricks of Example 2
[0073] Example 3
[0074] A pressure-free and firing-free brick prepared by synergistically recycling solid waste molten water quenching slag and sludge incineration ash, according to Figure 1 The specific steps are as follows:
[0075] 1) Place the water-quenched slag in a ball mill and mill it at a speed of 450 r / min for 1-2 h, and sieve the obtained water-quenched slag powder (100 mesh).
[0076] 2) Weigh the water-quenched slag powder and sludge incineration ash, place them in an oven, and dry them at 105 °C to constant weight;
[0077] 3) The water-quenched slag powder, sludge incineration ash and recycled aggregate were uniformly mixed in a mass ratio of 3.0:7.0:10.0, and stirred for 1 min (at a speed of 300 r / min) to obtain a mixed dry material;
[0078] 4) Prepare an alkali activator by mixing solid sodium hydroxide and liquid sodium silicate in a mass ratio of 0.5:4.0.
[0079] 5) Prepare an alkaline stimulating solution by mixing alkaline stimulating agent and deionized water in a ratio of 4.5:2.5 and let it stand for 24 hours.
[0080] 6) The prepared alkaline stimulating liquid and the mixed dry material are mixed in a ratio of 7.0:20.0 and stirred to obtain a fresh slurry (stirring for 2-3 min, rotating speed of 300 r / min), then poured into a 240 mm×115 mm×53 mm mold for vibration molding (vibration amplitude ≤ 5 mm, vibration frequency of 18-24 times / min, vibration time of 10-15 s), and then placed at 20±2 °C under sealed conditions for curing for 24 hours.
[0081] 7) After short-term curing, the blocks with a certain initial strength are demoulded and placed under standard conditions (temperature of 20±2 °C, relative humidity of more than 95%) for curing for 25-30 days to obtain the unfired brick products.
[0082] 8) After the curing period, the heavy metal leaching concentration of the product brick cementitious material is tested according to GB 5085.3-2007 "Identification Standard for Hazardous Waste Leaching Toxicity Identification", and the test results are shown in Table 6:
[0083] Table 6 Heavy metal leaching concentration of the cementitious material of Example 3
[0084] heavy metal Zn Pb Mn Cr Cd As Ni Cu Example 3 (heavy metal leaching concentration mg / L) 0.057 0.004 0.208 0.022 0.003 0.039 0.066 0.008
[0085] The obtained product bricks were subjected to performance tests according to GB / T 2542-2012 "Test methods for wall bricks". The physical performance test results of the product bricks are shown in Table 7:
[0086] Table 7 Physical properties of pressure-free and unfired bricks in Example 3
[0087] Example 4
[0088] A pressure-free and firing-free brick prepared by synergistically recycling solid waste molten water quenching slag and sludge incineration ash, according to Figure 1 The specific steps are as follows:
[0089] 1) Place the water-quenched slag in a ball mill and mill at a speed of 450 r / min for 1-2 h, and sieve the obtained water-quenched slag powder (100 mesh);
[0090] 2) Weigh the water-quenched slag powder and sludge incineration ash, place them in an oven, and dry them at 105 °C to constant weight;
[0091] 3) The water-quenched slag powder, sludge incineration ash and recycled aggregate were uniformly mixed in a mass ratio of 7.0:3.0:10.0, and stirred for 1 min (at a speed of 300 r / min) to obtain a mixed dry material.
[0092] 4) Solid sodium hydroxide and liquid sodium silicate are mixed in a mass ratio of 0.5:4.0 to prepare an alkali activator.
[0093] 5) Prepare an alkaline stimulating solution by mixing alkaline stimulating agent and deionized water in a ratio of 4.0:3.0 and let it stand for 24 hours.
[0094] 6) The prepared alkaline stimulating liquid and the mixed dry material are mixed in a ratio of 7.0:20.0 and stirred to obtain a fresh slurry (stirring for 2-3 min, rotating speed of 300 r / min), then poured into a 240 mm×115 mm×53 mm mold for vibration molding (vibration amplitude ≤ 5 mm, vibration frequency of 18-24 times / min, vibration time of 10-15 s), and then placed at 20±2 °C under sealed conditions for curing for 24 hours.
[0095] 7) After short-term curing, the blocks with a certain initial strength are demoulded and placed under standard conditions (temperature of 20±2 °C, relative humidity of more than 95%) for curing for 25-30 days to obtain the unfired brick products.
[0096] 8) After the curing period, the heavy metal leaching concentration of the product bricks was tested according to GB 5085.3-2007 "Identification of Hazardous Waste Identification Standards - Identification of Leaching Toxicity", and the test results are shown in Table 8:
[0097] Table 8 Heavy metal leaching concentration of the cementitious material of Example 4
[0098] heavy metal Zn Pb Mn Cr Cd As Ni Cu Example 4 (heavy metal leaching concentration mg / L) 0.007 0.012 0.001 0.004 0.000 0.086 0.001 0.007
[0099] The obtained product bricks were subjected to performance tests according to GB / T 2542-2012 "Test methods for wall bricks". The physical performance test results of the product bricks are shown in Table 9:
[0100] Table 9 Physical properties of pressure-free and unfired bricks of Example 4
[0101] Comparative Example 1
[0102] In this comparative example, the preparation steps of the brick body are the same as those in Example 1, except that: in this comparative example, no sludge incineration ash is added, and only water-quenched slag powder and recycled aggregate are used to prepare unburned bricks. The physical properties test results of the product bricks are shown in Table 10:
[0103] Table 10 Physical properties of pressure-free and unfired bricks of comparative example 1
[0104]
[0105] By comparing Example 1 and Example 1, it can be found that the proper addition of sludge incineration ash into the alkali-activated water-quenched slag system can improve the physical properties of the unfired bricks. This is because the filling effect and internal curing effect of the sludge incineration ash can inhibit the shrinkage effect and weathering phenomenon of the alkali-activated cementitious material to a certain extent, and due to the addition of sludge incineration ash with high specific surface area and high water absorption rate, the fluidity of the original slurry of the unfired bricks is reduced from 255 mm in Example 1 to 205 mm in Example 1, so that the fluidity reaches the optimal range, which is beneficial to the processing and forming hardening of the unfired bricks. Comparative Example 2
[0106] In this comparative example, the preparation steps of the brick body are the same as those in Example 1, except that: in this comparative example, no water-quenched slag powder is added, and only sludge incineration ash and recycled aggregate are used to prepare unburned bricks. The physical properties test results of the product bricks are shown in Table 11:
[0107] Table 11 Physical properties of pressure-free and unfired bricks in comparative example 2
[0108]
[0109] By comparing Example 1, Example 2, Example 3 and Comparative Example 2, it can be found that with the further increase of the content of sludge incineration ash, the compressive strength, 24 h water retention strength, flexural strength and other properties of the unfired brick will gradually decrease, the compressive strength is reduced from 33.6 MPa in Example 1 to 9.6 MPa in Comparative Example 2, the water retention strength is reduced from 28.5 MPa in Example 1 to 5.5 MPa in Comparative Example 2 (the high water retention strength of the embodiment proves that it has good water resistance), and the flexural strength is reduced from 4.7 MPa in Example 1 to 1.2 MPa in Comparative Example 2. This is because the reaction activity of sludge incineration ash is low, and its high content will lead to a significant reduction in the generation of aluminosilicate gel products, thereby affecting the mechanical properties of the brick body, and due to the porosity and high water absorption of sludge incineration ash, the higher the content of sludge incineration ash, the poorer the fluidity of the original slurry of the unfired brick, which is also not conducive to the preparation and molding hardening of the brick body. After comprehensive analysis, it is more appropriate to select a ratio of solid waste molten water quenching slag to sludge incineration ash in the range of 3.0-7.0: 7.0-3.0. Comparative Example 3
[0110] In this comparative example, the steps for preparing the brick body are the same as those in Example 1, except that the ratio of the alkaline activator to deionized water in the alkaline activating solution in this comparative example is 3.5:3.5. The test results of the physical properties of the product bricks are shown in Table 12:
[0111] Table 12 Physical properties of pressure-free and unfired bricks in comparative example 3
[0112]
[0113] By comparing Example 3 with Example 1 and Example 4, it can be found that in the alkali-activated water-quenched slag and sludge incineration ash system, reducing the amount of alkaline activator added will significantly affect the physical properties of the unfired bricks, resulting in a significant decrease in the compressive strength, water retention strength and flexural strength of the finished bricks. This is because the solid waste system of water-quenched slag and sludge incineration ash requires a certain alkaline environment to effectively stimulate its reaction. If the alkaline activator added is insufficient, the degree of reaction will be greatly reduced, thereby reducing the amount of silicate gel product generated, directly affecting the strength development; and with the increase in the amount of deionized water added, the fluidity of the original slurry of the unfired brick increases from 205 mm in Example 1 to 237 mm in Comparative Example 3, which is not conducive to the processing and forming hardening of the unfired bricks. Comparative Example 4
[0114] In this comparative example, the preparation steps of the brick body are the same as those in Example 1, except that the ratio of the alkaline activator to deionized water in the alkaline activating solution in this comparative example is 5.0:2.0. The test results of the physical properties of the product bricks are shown in Table 13:
[0115] Table 13 Physical properties of pressure-free and unfired bricks of comparative example 4
[0116]
[0117] By comparing Example 4 with Example 1 and Example 4, it can be found that excessive addition of alkaline activator will also significantly reduce the compressive strength, water retention strength and flexural strength of the unfired brick. This is because excessive alkaline activator will greatly increase the drying shrinkage effect of the alkali-activated cementitious material, increase the number of malignant cracks and pores inside the brick body, and inhibit the formation of hydrated calcium aluminosilicate gel, which contributes more to the strength. Comprehensive analysis shows that the ratio of alkaline activator to deionized water in the preparation of the alkaline activating solution of this system is more suitable at 4.0-4.5: 3.0-2.5.
[0118] All embodiments and comparative examples of the present invention were tested for heavy metal leaching concentration according to GB 5085.3-2007 "Identification of Hazardous Waste Identification Standards - Leaching Toxicity Identification", and it was found that the heavy metal leaching amount of the obtained unburned bricks was extremely low and basically risk-free, indicating that the preparation method provided by the present invention has excellent heavy metal solidification ability and reduces the harm of heavy metals in solid waste to the environment.
[0119] The preparation method provided by the present invention can obtain unburned bricks with good comprehensive performance. The density of the unburned brick obtained in Example 1 with the best performance is 1840 kg / m 3The original slurry fluidity is 205 mm, the 24 h water absorption is 9.5%, the compressive strength is 33.6 MPa, the 24 h water retention strength is 28.5 MPa, and the flexural strength is 4.7 MPa.
[0120] The above is only a preferred embodiment of the present invention. Although the present invention has disclosed the preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing pressure-free and fire-free bricks for synergistically recovering solid waste molten water quenching slag and sludge incineration ash, characterized in that: The following steps are involved: S1: placing the solid waste molten water-quenched slag in a ball mill, adding gypsum or grinding aids not exceeding 0.5% of the mass of the solid waste molten water-quenched slag, and grinding to the solid waste molten water-quenched slag powder of a specified fineness; S2: The solid waste molten water quenched slag powder, the sludge incineration ash, and the recycled aggregate are uniformly mixed in a mass ratio of 3.0-7.0: 7.0-3.0: 10.0 to obtain a mixed dry material, wherein the solid waste molten water quenched slag powder and the sludge incineration ash need to be dried to a constant weight before mixing; S3: preparing an alkaline stimulating solution by mixing alkaline stimulating agent: deionized water in a ratio of 4.0-4.5: 3.0-2.5; S4: mixing the prepared alkaline stimulating liquid with the mixed dry material and stirring to obtain a fresh slurry, then pouring it into a mold for vibration molding, and curing it under sealed conditions; S5: After short-term sealing and curing, the blocks with a certain initial strength are demoulded and placed under standard conditions for curing for 25-30 days to obtain the unsintered brick product; The particle size of the solid waste molten water quenched slag powder in step S1 includes a passing rate of 100% through a 100-mesh sieve, a passing rate of not less than 90% through a 150-mesh sieve, and a passing rate of not less than 55% through a 300-mesh sieve; The recycled aggregate in step S2 is any one of waste concrete, waste bricks, and waste ceramics, or a mixture of several of them; The particle size of the recycled aggregate in step S2 is continuously graded between 2.36 mm and 9.5 mm, wherein the mass ratio of the aggregates with particle sizes of 2.36 mm to 4.75 mm and 4.75 mm to 9.5 mm is 1:1; The alkaline activator in step S3 is solid sodium hydroxide and liquid sodium silicate in a mass ratio of 0.5:4.0; The pressure-free and unfired bricks have hydrated calcium aluminosilicate gel and hydrated sodium aluminosilicate gel as main hydration products, and the raw material formula is solid waste molten water quenching slag: sludge incineration ash: recycled aggregate: alkaline stimulating liquid = 3.0-7.0: 7.0-3.0: 10.0: 7.0 by mass; The unsintered brick has a compressive strength of 24.3-33.6 MPa, a 24-hour saturated strength of 18.8-28.5 MPa, a flexural strength of 3.4-4.7 MPa, and a 24-hour water absorption rate of less than 15%.
2. The method for preparing pressure-free and firing-free bricks for collaboratively recovering solid waste molten water quenching slag and sludge incineration ash according to claim 1, characterized in that: In the step S1, the water content of the solid waste molten water quenched slag is ≤10%, the ball milling speed is 300-450 r / min, and the ball milling time is 1-2 h.
3. The method for preparing pressure-free and firing-free bricks for collaboratively recovering solid waste molten water quenching slag and sludge incineration ash according to claim 1, characterized in that: The gypsum in step S1 complies with the gypsum or mixed gypsum of Class G or Class M grade 2 or above specified in GB / T 5483, and the grinding aid complies with the provisions of GB / T 26748.
4. The method for preparing pressure-free and firing-free bricks for collaboratively recovering solid waste molten water quenching slag and sludge incineration ash according to claim 1, characterized in that: The standard curing temperature in step S5 is 20±2°C, the relative humidity is above 95%, and the time is 25 to 30 days.
Citation Information
Patent Citations
Alkali-activated high-titanium content slag small-sized hollow block and preparation method thereof
CN107651924A
Preparation method of clinker-free baking-free environment-friendly brick doped with sludge incineration ash
CN113582592A